Long-term care insurance and integrated care for the aged in Japan - Matsuda, Shinya (Igitur, Utrecht Publishing & Archiving, 2001)
By the introduction of a public, mandatory program of Long-Term Care Insurance (LTCI) on April 1, 2000, Japan has moved towards a system of social care for the frail and elderly. The program covers care that is both home-based and institutional. Fifty percent of the insurance is financed from the general tax and the other fifty percent from the premiums of the insured. The eligibility process begins with the individual or his/her family applying to the insurer (usually municipal government). A two-step assessment process to determine the limit of benefit follows this. The first step is an on-site assessment using a standardised questionnaire comprising 85 items. These items are analysed by an official computer program in order to determine either the applicant's eligibility or not. If the applicant is eligible it determines which of 6 levels of dependency is applicable. The Japanese LTCI scheme has thus formalised the care management process. A care manager is entrusted with the entire responsibility of planning all care and services for individual clients. The introduction of LTCI is introducing two fundamental structural changes in the Japanese health system; the development of an Integrated Delivery System (IDS) and greater informatisation of the health system.